2019
DOI: 10.3325/cmj.2019.60.255
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Croatian physicians: a cross-sectional national survey

Abstract: Aim To investigate the prevalence of burnout syndrome among physicians of all specialties, including residents and non-specialists, on a national level in Croatia. Methods This cross-sectional study, conducted in October 2017, used anonymous online survey based on the Maslach Burnout Inventory Human Services Survey. The Croatian version of the inventory was assessed for acceptability, factorial validity, and reliability. Key dimensions of burnout – emotional exhaustion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Another survey based on MBI, conducted among primary health care providers in the Sarajevo Canton, showed that 25.3% of HCWs experienced a high level of emotional exhaustion and 17.7% experienced depersonalization ( 37 ). Research conducted among physicians in Croatia on a national level before the pandemic showed that 63% of all physicians experienced burnout, and 16% of physicians experienced all three forms of burnout ( 38 ). The research on the levels of burnout syndrome in critical care nurses in Croatia showed that 22.1% of nurses expressed a high level of emotional exhaustion, with a lower level of depersonalization (7.9%), and 34.5% had a low level of personal accomplishment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another survey based on MBI, conducted among primary health care providers in the Sarajevo Canton, showed that 25.3% of HCWs experienced a high level of emotional exhaustion and 17.7% experienced depersonalization ( 37 ). Research conducted among physicians in Croatia on a national level before the pandemic showed that 63% of all physicians experienced burnout, and 16% of physicians experienced all three forms of burnout ( 38 ). The research on the levels of burnout syndrome in critical care nurses in Croatia showed that 22.1% of nurses expressed a high level of emotional exhaustion, with a lower level of depersonalization (7.9%), and 34.5% had a low level of personal accomplishment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted initially in Croatia as part of a bigger national project for assessment of burnout among Croatian physicians. 14 It was supported under the auspices of the Croatian Medical Chamber, the independent body that regulates medical practice in Croatia. Given the overwhelming response among physicians in Croatia, a decision was made to expand the study to neighboring countries of Eastern Europe, primarily those that share similar historical and societal postcommunist transition backgrounds.…”
Section: Participant Samplementioning
confidence: 99%
“…A study done by Vanja Pintarić, et al reported 16% of respondents simultaneously experienced high levels on all three burnout dimensions [15]. Burnout syndrome among physicians was estimated to range from 2.4% to 72% (Roth, et al) [13,14] but much lower than what was estimated in Aldrees, et al which reported a prevalence of 33% [16] Goehring, et al showed prevalence of 4% despite the fact that all the afore mentioned studies used the same criteria for diagnosing burnout syndrome; they reported different results, which can be referred to variations in cultures and health care nature [17].…”
Section: Discussionmentioning
confidence: 99%